2015
DOI: 10.1159/000439586
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Polyautoimmunity among Patients with Celiac Disease: A Cross-Sectional Survey

Abstract: Aim: To define the prevalence of polyautoimmunity (PAI) among celiac disease (CD) patients and to compare clinical and laboratory features of CD patients with or without PAI in order to determine the risk factors for PAI in CD. Material and Method: Patients diagnosed with CD in our clinic between 2007 and 2014 with at least 1 year of follow-up were retrospectively evaluated. Totally 145 patients were included in the study. Information on patient demographics and laboratory data were obtained from patient recor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 55 publications
2
8
0
Order By: Relevance
“…Notable, young patients in the present study (Groups FI and MI) were diagnosed with IMDs before the diagnosis of CD, which is consistent with a report by Demirezer et al in Turkey (24) . Demirezer and colleagues identified female sex, family history of AIDs as risk factors for IMDs, as presented in the present study.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Notable, young patients in the present study (Groups FI and MI) were diagnosed with IMDs before the diagnosis of CD, which is consistent with a report by Demirezer et al in Turkey (24) . Demirezer and colleagues identified female sex, family history of AIDs as risk factors for IMDs, as presented in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Interestingly, three or four IMDs occurring in the same patient is a rare association (29) . Compared with controls, patients with CD were 11.4 times more likely to develop Addison's disease before or after the diagnosis of CD (24) . In this study, one female (age, 49 years) and one male (age, 61 years) presented with Addison's disease at the diagnosis of CD.…”
Section: Discussionmentioning
confidence: 91%
“…studied 520 CD patients, and the most common AIDs seen in their study population were psoriasis, Hashimoto's thyroiditis and Sjögren's syndrome . Bolat et al investigated 145 CD patients by means of polyautoimmunity, and found that 33% of their patients had polyautoimmunity and 10.3% had multiple autoimmune syndrome . They also reported that female sex, family history of an AID, vitamin D deficiency, anti‐gliadin IgG positivity, antinuclear antibody positivity >1/80 titer and having a musculoskeletal disease were risk factors for polyautoimmunity.…”
Section: Discussionmentioning
confidence: 99%
“…The relative risk of associating one or more autoimmune pathologies is approximately three times higher in CD patients when compared to general population [14] and 30% of the CD patients have also another immune pathology [15]. Together with the musculoskeletal involvement, the female gender, DGP positivity, vitamin D deficiency and antinuclear antibody positivity were associated with polyautoimmunity in CD patients [15]. The following mechanisms might explain the increased autoimmunity expression in CD: similar genetic features, common triggers, or the disturbed intestinal permeability [16].…”
Section: Dear Editormentioning
confidence: 99%